Childhood and the right to happiness: Legal scope and the support network in Arapiraca - Bezerra, Mahely Corrêa; de Melo, Lenivaldo Manoel; da Silva, Lucicleide; Neto, Júlio Gomes Duarte; da Silva, Marcos Alexandre (Seven Editora, 2024)
The article addresses the results of the extension project of the State University of Alagoas – UNEAL, "Protected Child is Happy Child", whose objective was to identify the dynamics of the functioning of the child support network in the municipality of Arapiraca in the state of Alagoas, as well as the measurement of the types and dimension of violence practiced/identified. The praxis of extension implied the holding of workshops in toy libraries and early childhood education schools for the dissemination and distribution of an educational booklet produced after dialogue with actors of the existing protection network in the municipality, in the security forces and in the judiciary. A study of the statistical data of the care records carried out by the protection network in the years 2020; 2022 and 2023 (Children's Police Station, the Guardianship Councils of Arapiraca and the Sipia and DataSUS system) indicates a higher incidence of violence against children in poorer neighborhoods, but cases are identified in all neighborhoods, regardless of the purchasing power of their population. In the categorization of the types of violence, negligence was identified as a strong reason for families to go to the Guardianship Council; next, school education; then psychological or physical aggression; life & health or drugs; and sexual abuse. Interestingly, the mother is identified as the aggressor in a large number of cases. Symmetry is observed in the informants' databases, and the lack of daycare centers and full-time school is identified in some neighborhoods of the municipality, catalyzing intrafamily violence. DOI:https://doi.org/10.56238/sevened2024.014-018